Investigating the Inequality in Distribution of Otorhinolaryngology- Head & neck surgery Specialists in the Provinces of Iran In 2017 - Ali Akbari Sari; Mahboubeh Bayat; Mohammad Arab; Mehdi Yaseri; Seyedeh Fatemeh Hosseini (Tehran University of Medical Sciences, 2020)
Background: equality in access of health care services is one of the most important goals of Health system .In this study, we provided a description of the distribution of Otorhinolaryngology Head & neck surgery specialists in the Provinces of Iran in 2017. Materials & Methods: This descriptive-analytical study was conducted in 2017 to describe the distribution of Otorhinolaryngology Head & neck surgery specialists in the Provinces of Iran in 2017. Data were gathered through Ministry of Health and Statistical Center of Iran. Gini Coefficient, Concentration Curve ,Multiple Regression and Geographic Maps used by Microsoft R Version 3-6-0 for data analysis. Results: The highest and lowest ratio of Otorhinolaryngology Head & neck surgery specialists per population in the year 2017 was reported in Tehran (2.31 per 100,000 populations) and Hormozgan (0.39 per 100,000 populations). Conclusion: There was a considerable disparity between different regions of the country in terms of access to Otorhinolaryngology specialists.